2020
DOI: 10.3390/nu12072039
|View full text |Cite
|
Sign up to set email alerts
|

Minimum Dietary Diversity for Women of Reproductive Age (MDD-W) Data Collection: Validity of the List-Based and Open Recall Methods as Compared to Weighed Food Record

Abstract: Minimum dietary diversity for women of reproductive age (MDD-W) was validated as a population-level proxy of micronutrient adequacy, with indicator data collection proposed as either list-based or open recall. No study has assessed the validity of these two non-quantitative proxy methods against weighed food records (WFR). We assessed the measurement agreement of list-based and open recall methods as compared to WFR (i.e., reference method of individual quantitative dietary assessment) for achieving MD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
59
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 40 publications
(62 citation statements)
references
References 14 publications
3
59
0
Order By: Relevance
“…Yet, it remained much higher compared to women asylum seekers in Norway, a high-income country (49%) (69) . Hanley-Cook et al showed evidence of overreporting of food groups by 10% to 16% for assessing the prevalence of Minimum Dietary Diversity for Women of Reproductive Age (MDD-W) using the list-based or open recall methods (74) . This suggests that the prevalence of LDD can be even higher in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Yet, it remained much higher compared to women asylum seekers in Norway, a high-income country (49%) (69) . Hanley-Cook et al showed evidence of overreporting of food groups by 10% to 16% for assessing the prevalence of Minimum Dietary Diversity for Women of Reproductive Age (MDD-W) using the list-based or open recall methods (74) . This suggests that the prevalence of LDD can be even higher in our study.…”
Section: Discussionmentioning
confidence: 99%
“…The first limitation of our observational analysis is the single 24HR, obtained from a relatively small sample of young adults in Tirana. Although 24HRs provide a higher degree of accuracy for assessing food and nutrient intake relative to food frequency questionnaires, such dietary assessment methods are prone to measurement error due to respondent memory lapses and social desirability/approval of specific food and drinks (62) . Moreover, 24HRs are appropriate to estimate population average dietary intakes, but do not account for intra-person variability (63) and thus estimation of usual dietary intake (64) .…”
Section: Discussionmentioning
confidence: 99%
“…The indicator is dichotomous, with the threshold for achieving minimum dietary diversity set at a score of ≥5. A comparison of the recall and a list-based method against a weighed food intake record revealed that both methods are likely to over-report the number of women achieving the minimum score (29) . In a study of dietary diversity in a resource poor setting in Pakistan, we reported that MMD-W was not achieved by most of the participants.…”
Section: Increasing Dietary Diversitymentioning
confidence: 99%